THE HISTORY OF ORIGIN OF VENTURE INVESTMENTS - Зражевець, Є. Є. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2013)
In the article are analyzed basic reasons of origin venture investments in the USA. The venture investing in Ukraine is founded in 1992 and now it is in the stage of forming. An author offered the ways for development of market of venture investments in Ukraine